Koherensi Paragraf dalam Skripsi Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia - Anie Wulandari Azis (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
This study was proposed to identify and analyze the markers and the coherence of the paragraphs of the students’ theses of Indonesian Language and Literary Education Program. It was a qualitative study using a discourse analysis method. The data were texts in paragraphs selected from 30 students’ theses especially the Introduction Chapter. The study found that there were 272 coherent paragraphs and 34 incoherent paragraphs. findings were theses, results shown that there were five coherence markers found in the samples. Those were repetition, substitution, pronoun, conjunction, and causal relation. There were also found that the coherent paragraphs consisted of explicit coherence (213 data) and implicit coherence (59 data). The explicit coherences were developed with those 5 coherence markers and the repetition was the most dominant markers in use. By comparing the number of the coherent paragraphs with the incoherent paragraphs, it can be drawn that the coherence of the students’ writing in introduction chapter was categorized into very good level.